PERTANGGUNGJAWABAN AKTA NOTARIS SEBAGAI AKTA AUTENTIK SESUAI DENGAN UNDANG-UNDANG JABATAN NOTARIS - Gladys Natalie Aurielle Sirait; Benny Djaja (LPPM Universitas Ekasakti Padang, 2023)
Notaries are public officials who have the right to make authentic deeds that can be used as evidence in a civil case. Law No. 30 of 2004 explains that a Notary is a public official who has the authority to make authentic deeds and has other powers as described in the Law. Notary is the right hand of the state where a Notary must carry out his duties in the field of Civil Law in Indonesia, the Government aims to provide legal guarantees in terms of private law for residents who have given some of their authority to Notaries to make authentic deeds. Therefore, when performing their duties, Notaries must act as responsible public officials. Based on its form, the deed is divided into two parts, namely authentic deeds and underhand deeds. An authentic deed is a deed made by an official who has been given the power or authority by the state/government based on predetermined provisions, either with or without the assistance of those who have an interest, and records what is requested by those concerned. Meanwhile, the deeds of the parties are made at the initiative of the party who comes to the official, such as power of attorney deeds, land title deeds, and sale and purchase deeds. An authentic document is considered the most powerful and complete evidence. It establishes a clear legal relationship between the parties regarding rights and obligations. Notaries are public officials who are authorized to create authentic documents and other duties in accordance with the Law. It is perfect and binding for the judge must consider it as a complete and sufficient basis of fact to make a decision in the settlement of a disputed case